2014
DOI: 10.1371/journal.pone.0106025
|View full text |Cite
|
Sign up to set email alerts
|

Development of β-Lactoglobulin-Specific Chimeric Human IgEκ Monoclonal Antibodies for In Vitro Safety Assessment of Whey Hydrolysates

Abstract: BackgroundCow’s milk-derived whey hydrolysates are nutritional substitutes for allergic infants. Safety or residual allergenicity assessment of these whey hydrolysates is crucial. Currently, rat basophilic leukemia RBL-2H3 cells expressing the human IgE receptor α-chain (huFcεRIα-RBL-2H3), sensitized with serum IgE from cow’s milk allergic children, are being employed to assess in vitro residual allergenicity of these whey hydrolysates. However, limited availability and inter-lot variation of these allergic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Furthermore, in our basophil activation experiments, glycation of BLG reduced its capacity to crosslink FcεRI receptors on RBL cells. In extensively glycated BLG, all residues containing free amino group (16 lysines, two arginines, and N‐terminal amino group of Leu 1) seem to be glycated, while all of the BLG‐specific chimeric human IgE monoclonal antibodies used in this study recognize peptides containing at least 1–2 residues with possible glycation sites . Therefore, it is highly likely that extensive BLG glycation reduced mAb IgE binding by changing epitope structure, and led to reduced basophil activation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, in our basophil activation experiments, glycation of BLG reduced its capacity to crosslink FcεRI receptors on RBL cells. In extensively glycated BLG, all residues containing free amino group (16 lysines, two arginines, and N‐terminal amino group of Leu 1) seem to be glycated, while all of the BLG‐specific chimeric human IgE monoclonal antibodies used in this study recognize peptides containing at least 1–2 residues with possible glycation sites . Therefore, it is highly likely that extensive BLG glycation reduced mAb IgE binding by changing epitope structure, and led to reduced basophil activation.…”
Section: Discussionmentioning
confidence: 85%
“…EXiLE assay was performed as described previously with slight modifications. RS‐ATL8 cells (5 × 10 4 cells per 50 μL per well) in 96‐wells flat bottom culture plate were sensitized overnight with a pool of six anti‐BLG chimeric IgE monoclonal antibodies (1 μg mL −1 each individual humanized IgE) . Cells were washed once with sterile PBS and then stimulated for 1 h at 37 °C in a 5% CO 2 incubator with 50 μL per well of native and glycated BLG diluted in MEM containing 10% FCS in four different concentrations (1, 10, 100, and 1000 ng mL −1 ) or with 1 μg mL −1 goat anti‐human IgE antibodies (DakoCytomation, Glostrup, Denmark) as control.…”
Section: Methodsmentioning
confidence: 99%
“…This assay was developed with IgE directed against "allergenic" immunodominant regions/epitopes on bovine BLG, also recognized by serum IgE from CMPA infants. 7 A detailed description of the laboratory methods is provided in Table S2.…”
Section: Peptide Size Profile and Residual Immunogenic Milk Protein Omentioning
confidence: 99%
“…As previously described [5,14], the antibodies used in the flow cytometry analysis included anti-dog CD4 rat antibody labeled with Alexa Fluor 647 (Clone YKIX302.9) (Bio-Rad Laboratories, Inc., Hercules, CA, USA), and anti-human CD25 antibody labeled with phycoerythrin (Clone ACT-1) (DAKO Cytomation, Glostrup, Denmark), as well as isotype controls such as Alexa Fluor 647-labeled purified rat IgG2a (Bio-Rad Laboratories), and PE-labeled mouse IgG1 (Bio-Rad Laboratories). Stained dead cells were excluded by propidium iodide incorporation.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Flow cytometry analysis revealed that the type IV lymphocytes associated with hypersensitivity were CD4 + helper T-lymphocytes [5,21]. Theoretically, these types of lymphocytes are reactive to proteins or peptides that do not induce IgE-mediated reactions [10,14]. Therefore, it is clear that clinical use of hydrolyzed diets, as part of food elimination programs, may not be appropriate for all dogs with food hypersensitivity.…”
mentioning
confidence: 99%